Exceptionally large juvenile xanthogranuloma – a case report - Luka Bulić; Eva Brenner; Suzana Ožanić Bulić (Liječnički vjesnik, 2023)
Juvenile xanthogranuloma (JXG) is a rare, benign skin lesion pathologically classified as a non-Langerhans cell histiocytosis. The lesions appear within the first year of life in 75% of patients, predominantly on the head or neck, growing up to 5mm in size. While the etiology is mostly infectious, it can also be caused by genetic variants. In most patients, the condition has an easy course and resolution. Histopathological features include a histiocytic invasion of the superficial dermis, with additional eosinophils, lymphocytes and plasma cells. The lesion typically stains with anti-CD4, anti-XIIIa and CD68 markers.